A Survey on Phytochemical Composition and Biological Activity of Zygophyllum fabago from Iran - Saeid Yaripour; Mohammad-Reza Delnavazi; Parina Asgharian; Samira Valiyari; Saeed Tavakoli; Hossein Nazemiyeh (Tabriz University of Medical Sciences, 2017)
Purpose: Zygophyllum fabago L. (Z. fabago) is a widespread perennial herb which is used as a medicinal plant in traditional medicine of Iran, Turkey and China. The present study was a survey on phytochemical constituents and biological activities of this plant. Methods: Methanolic extract of the roots was fractionated over a C-18 pre-packed cartridge (Sep-pak) and chromatographic separation was performed on a reversed-phase preparative HPLC. Structural elucidation of the isolated compounds was carried out using UV, 1H-NMR and 13C-NMR spectral analyses. Furthermore, the chemical compositions of the essential oil of the aerial parts were identified by GC-MS analysis. Antiproliferative and antioxidant activities of all extracts from aerials were determined by MTT and DPPH assays, respectively. Results: Phytochemical investigation on the plant roots led to the isolation and identification of two the 60% methanol-water Sep-pak fraction, a prenylated flavone glycoside, 6-C-prenyl-7-O-[ β -D-4'''-O-acetyl-glucopyranosyl-(1'''→2'')-β-D-glucopyranosyl] apigenin, which was named as a Zygocaperoside and also, other flavonoid, was named as the Isorhamnetin -3-O glucoside. None of the extracts showed antiproliferative effect against cancerous cells. However, among the extracts, methanolic extract indicated antioxidant activity. Moreover, essential oils of flowers and leaves of plant have high amounts of sesquiterpene hydrocarbons and diterpenoides. Conclusion: The results of present study introduce Z. fabago roots as a new source of flavonoid glycosides and suggest it as an appropriate candidate for further pharmacological studies.